Early Childhood Programs for Non-English Speaking Children. OCD Topical Paper - Bernbaum, Marcia; ERIC Clearinghouse on Elementary and Early Childhood Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Guidelines based on research and reports from bilingual preschool programs are offered to assist teachers and administrators interested in the general problems of bilingualism and bilingual education. In addition to summarizing research and describing existing models for bilingual preschool programs (citing references to additional sources of information) this document lists recommended teacher-administrator handbooks and useful materials for teachers. Model bilingual programs are classified both as to composition of the classes (whether all are non-English speaking or not) and as to approach. Among the program approaches described are the Michigan Oral Language Program for Spanish-speaking migrant children, a nursery school on a Ute reservation in Utah, an elementary school which focuses equally on Navaho and English, and the Tucson Early Education Model of the University of Arizona. The document concludes with a list of reference sources developed during 1965-1970. (WY)
Sponsoring Agency: National Center for Educational Communication (DHEW/OE), Washington, DC. Div. of Information Resources.
Sponsoring Agency: Office of Child Development (DHEW), Washington, DC.
Contract Number: OEC-0-70-2623(519).
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Bilingual Schools; Bilingual Students; Bilingualism; Educational Media; Educational Policy; English (Second Language); Guides; Non English Speaking; Preschool Education; Program Descriptions; Research; Second Language Learning; Project Head Start